2020
DOI: 10.3168/jds.2019-17644
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Characterization of molasses chemical composition

Abstract: Beet and cane molasses are produced worldwide as a by-product of sugar extraction and are widely used in animal nutrition. Due to their composition, they are fed to ruminants as an energy source. However, molasses has not been properly characterized in the literature; its description has been limited to the type (sugarcane or beet) or to the amount of dry matter (DM), total or water-soluble sugars, crude protein, and ash. Our objective was to better characterize the composition of cane and beet molasses, exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(114 citation statements)
references
References 25 publications
4
100
1
9
Order By: Relevance
“…In molasses intended for fermenting purposes, some of these factors can be controlled by standardization practices, while other factors can be more difficult to regulate. A recent publication has also noted that molasses has yet to be properly characterised, and that its description has mostly been limited to either the type of the origin sugarcane or beet, the amount of dry matter, total or water-soluble sugars, crude protein, and ash [86]. This means that a multivariate pool, including environmental factors affects the chemical composition of molasses.…”
Section: Feedstock Variationmentioning
confidence: 99%
“…In molasses intended for fermenting purposes, some of these factors can be controlled by standardization practices, while other factors can be more difficult to regulate. A recent publication has also noted that molasses has yet to be properly characterised, and that its description has mostly been limited to either the type of the origin sugarcane or beet, the amount of dry matter, total or water-soluble sugars, crude protein, and ash [86]. This means that a multivariate pool, including environmental factors affects the chemical composition of molasses.…”
Section: Feedstock Variationmentioning
confidence: 99%
“…Sugar beet and cane molasses are abundant liquid by-products from the sugar industry, which are generally found at high amount of total sugars (50.6-71.0% w/w) and traces of micronutrients such as minerals (Ca, Mg, Na and K), phosphate and nitrogen compounds [14]. These sugar-rich solutions does not require any major physical or chemical pretreatment (such as hydrolysis, filtration, sterilization, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Chosen cane molasses came from Central America, Asia and Europe, while beet molasses from Europe, North America and Africa. Samples were analysed for their chemical composition as described in a previous paper (Palmonari et al 2020), and the results are reported in Table 1. In particular, DM was determined according to AOAC 934.01 official method.…”
Section: In Vitro Fermentationsmentioning
confidence: 99%
“…Overall, molasses could be added to the diets in substitution of starch sources, due to a different impact on rumen fermentations and pH (Oelker et al 2009;Brito et al 2017;De Ondarza et al 2017), effect related to their sugar fraction composition. Molasses contain mono-di-, and tri-saccharides, composed by hexoses, as well as pentoses in traces (Palmonari et al 2020). Thus, it could be assumed that each one of these compounds would have a different fermentation patter or rate, depending on the complexity of the molecule, and its structure.…”
Section: Introductionmentioning
confidence: 99%